2014
DOI: 10.1093/eurheartj/ehu506
|View full text |Cite
|
Sign up to set email alerts
|

A study of implanted cardiac rhythm recorders in advanced cardiac AL amyloidosis

Abstract: The discovery that bradyarrhythmias heralded terminal cardiac decompensation in most patients with severe cardiac AL amyloidosis supports a study of prophylactic pacemaker insertion in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(109 citation statements)
references
References 25 publications
1
98
1
9
Order By: Relevance
“…5 Patients in G1 had increased PR interval (mean of 0.230s ± 0.060), which was significantly different from G2 (p=0.015), G3 (p=0.044) and G4 (p=0.005). Sayed et al 22 also showed an association between disturbances in electrical conduction and decreased longitudinal strain, and a negative prognostic value for this association, although the study was conducted with cardiac AL amyloidosis.…”
Section: Discussionmentioning
confidence: 98%
“…5 Patients in G1 had increased PR interval (mean of 0.230s ± 0.060), which was significantly different from G2 (p=0.015), G3 (p=0.044) and G4 (p=0.005). Sayed et al 22 also showed an association between disturbances in electrical conduction and decreased longitudinal strain, and a negative prognostic value for this association, although the study was conducted with cardiac AL amyloidosis.…”
Section: Discussionmentioning
confidence: 98%
“…However, pacemaker insertion failed to salvage patients with bradyarrhythmias in a study of newly diagnosed patients with severe symptomatic cardiac AL amyloidosis [59]. …”
Section: Treatmentmentioning
confidence: 99%
“…46,47 The benefit of ILR-guided therapy in patients at high risk of sudden cardiac death, 2 Data on ILR use in these rare diseases are limited and mainly retrospective [48][49][50] and the safety of an ILR approach for distinguishing benign causes of syncope and palpitations from lifethreatening arrhythmias requiring an ICD or a pacemaker should be evaluated in clinical trials.…”
Section: Ongoing Studies On the Prognostic Value Of Loop Recordersmentioning
confidence: 99%